A study of the user experience while working with mobile applications cooperating with sports bands - Szymon Czopek; Mariusz Dzieńkowski (Journal of Computer Sciences Institute)
The article analyses user experience while using two mobile applications, FitPro and Zepp Life that work with sports bands designed to monitor physical activity. As part of the study, the users were asked to perform tasks during which they used each app’s features. During the same research scenario, first on the first application and then on the second application, the user’s eye activity was recorded by means of the eyetracker. Then, each participant took part in a survey. Task completion time, eye-tracking indicators (the number of fixations, fixation duration, the number of blinks), users’ evaluation and the level of diagnosed errors were used for comparative analysis. All the results confirmed that the FitPro application, despite containing fewer features, was more intuitive, easier to use, more efficient, had a clear interface and, as a result, was better rated by the users.